Penguatan Digital Branding UMKM Melalui Pengelolaan Konten Media Sosial (Studi Pengabdian pada Geprek Bowtie Syahrijal dan Pentol Es Gudir Dharmahusada) - Josephine Maharani Virgiawan; Mohammad Hilmi Bayhaqi; Tommy Rizqi Akbar Purnama; Anak Agung Ayu Zahra Laylia Cantika; Norman Iskandar; Moh. Dey Prayogo (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The evolution of the digital era requires Micro, Small, and Medium Enterprises (MSMEs) to adapt by employing social media-based marketing strategies. However, many MSMEs have yet to fully leverage digital media to build their brand image or business identity. Addressing this issue, this community service initiative aims to enhance digital branding quality by creating more engaging social media content and optimizing digital promotions for two partners: Geprek Bowtie Syahrijal and Pentol Es Gudir Dharmahusada. The project employed a participatory approach involving direct observation, step-by-step guidance for business owners, and the implementation of social media content strategies. The results demonstrate positive changes, including improved visual content quality, more consistent brand identity, and increased interest from potential customers in both MSMEs. The mentoring model implemented here is expected to serve as a reference and example for future digital branding support for other MSMEs.